Some Bioactive Compounds and Antioxidant Activities of the Bitter Almond Kernel (Prunus dulcis var. amara) - Keser, Serhat; Demir, Ersin; Yilmaz, Okkes (Chem Soc Pakistan, 2014)
In this study, it was determined antioxidant activities and phenolic, flavonoid, phytosterol, lipid soluble vitamin and fatty acid contents of bitter almond kernel extract (BAE). Antioxidant activities of BAE was investigated by DPPH center dot, ABTS(center dot+), OH center dot radical scavenging, metal chelating activity and determination of lipid peroxidation levels (TBARS). BAE was scavenged 83.49% of the ABTS radical, 68.34% of the hydroxyl radical, and 68.65% of the DPPH radical. This extract was shown 49.36% of the metal chelating activity. Myricetin (1831.52 mu g/g), kaempferol (104.52 mu g/g), naringenin (2.51 mu g/g), vanillic acid (91.70 mu g/g), caffeic acid (85.92 mu g/g), ferulic acid (27.11 mu g/g) rosmarinic acid (0.95 mu g/g), hydroxycinnamic acid (1.35 mu g/g), delta-tocopherol (4.95 mg/kg), alpha-tocopherol (104.15 mg/kg), vitamin K (42.25 mg/kg), beta-sitosterol (366.95 mg/kg) and stigmasterol (242.65 mg/kg) were determined in the BAE. The major fatty acids were oleic acid (70.61%) and linoleic acid (20.68%) in the BAE. These results indicate that bitter almond can be a good natural source of fatty acids, lipid soluble vitamins, phytosterols, flavonoid, phenolic compounds.
Keywords: Bitter almond; DPPH; ABTS; Fatty acid; Flavonoid; Vitamin; Phytosterol